Examining Determinants of Leadership Style among Montenegrin Managers - Lojpur Anđelko; Aleksić Ana; Vlahović, Sanja; Pejić Bach Mirjana; Peković Sanja (Naše gospodarstvo/Our economy, 2015)
As a leader’s behavior can have a strong impact on different employee work- related outcomes, various approaches have been put forth in an effort to determine the most effective form of leadership and determinants of individuals’ choice of leadership style. This paper analyzed whether one’s choice of leadership style is due more to personal or organizational characteristics. We used survey data to investigate the determinants of leadership style among Montenegrin managers. Our analysis showed that, although demographic characteristics such as gender, age, and education do not influence the choice of leadership style, internal organizational characteristics such as hierarchical level, managerial orientation to tasks/people, and decision-making characteristics such as decision- making style and decision-making environment are positively associated with the choice of democratic leadership style. This contributes to recent research in leadership that shows how some personal characteristics are considered to be less important in developing certain styles and that the choice of style is more dependent and contingent on external influences and situations.